Educational diversity, organizational structure and innovation performance: Evidence from Uruguayan industry - Bello-Pintado, Alejandro; Bianchi, Carlos (Estudios de Economía, 2018)
This paper analyses the relationship between horizontal educational diversity (HED) and firm innovation performance, both in the propensity to innovate and the intensity of innovation in firm performance. Moreover, we hypothesise that the organizational structure of the firm moderates this relationship. Using panel data from the Uruguayan Innovation Survey 2006-2012, econometric estimates show that HED is barely associated with innovation performance in products and processes. We found that advanced organisational structures of the firm positively moderate the former relationship, but only for firms achieving radical innovations.